2022
DOI: 10.3389/fpls.2022.856442
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Plant Hormones, Metal Ions, Salinity, Sugar, and Chemicals Pollution on Glucosinolate Biosynthesis in Cruciferous Plant

Abstract: Cruciferous vegetable crops are grown widely around the world, which supply a multitude of health-related micronutrients, phytochemicals, and antioxidant compounds. Glucosinolates (GSLs) are specialized metabolites found widely in cruciferous vegetables, which are not only related to flavor formation but also have anti-cancer, disease-resistance, and insect-resistance properties. The content and components of GSLs in the Cruciferae are not only related to genotypes and environmental factors but also are influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 231 publications
(301 reference statements)
0
7
0
Order By: Relevance
“…In both plants and animals, Trp is a precursor of melatonin [ 33 , 34 ]. Melatonin can not only effectively treat sleep disorders in humans, it also plays an important role in plant growth and stress resistance [ 25 ]. Thus, the concentration of melatonin and the three intermediates in its biosynthetic pathway ( Figure 1 E) was measured.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In both plants and animals, Trp is a precursor of melatonin [ 33 , 34 ]. Melatonin can not only effectively treat sleep disorders in humans, it also plays an important role in plant growth and stress resistance [ 25 ]. Thus, the concentration of melatonin and the three intermediates in its biosynthetic pathway ( Figure 1 E) was measured.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, broccoli seedlings are not an ideal source of melatonin for a daily diet. Nevertheless, melatonin was reported to be highly effective at scavenging ROS in plants under various environmental stresses [ 25 ]; thus, the augmentation of melatonin through Trp treatment could improve a plant’s adaptability to adversity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It accomplishes these goals by acting directly or indirectly on substances that control important ripening genes, other plant hormones, transcription factors, sugars, and polyamines (Kou et al, 2021). It supports growth and productivity, as well as maintaining quality postharvest may be attributed to works as a multipurpose mediator of numerous physiological processes (Gupta et al,2022, Liu et al, 2022and Shibata and Sugimoto, 2019 cleared that ABA supports shoot growth, plants' root growth and leaf senescence are promoted. Furthermore, Miret et al (2018) and Zhao et al (2016) showed that ABA promotes and protects chloroplast functionality.…”
Section: Introductionmentioning
confidence: 99%